Study on Srimad Bhagavad Gita's Slokas no. 47 of Chapter 2 that in Sanskrit "Karmanye Dhikaraste Maa Phaleshu Kadachana…" in Relation to Life and Its Meanings - Dr. Ashutosh Mishra (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Karmanye in English means the work that is performed by people or living beings. In science as part of thermodynamics the work related to energy in other words work done is the process of change in energy levels or its form. Further life is a collective and coordinated vital activity like sensitivity, adaptation, growth, metabolism, respiration, excretion and reproduction. Those show life commonly called living beings. For the scientific community life is still a matter of research because still they do not explain with full clarity how life comes and where life goes after death and what is the meaning of birth and death in social prospects. The Srimad Bhagavad Gita is a book that gives with clarity and explains reasonably the questions related to life and its meanings .In this above said context I have taken the present study.